The skill matching challenge : analysing skill mismatch and policy implications - (:unkn) unknown (Publications Office of the European Union, 2010)
"Skill mismatch is a complex phenomenon affecting individuals, enterprises, economies and societies; it does not only refer to skill gaps and skill shortages, but also to skills exceeding job requirements. This report aims to structure the currently scattered evidence on skill mismatch by analysing seven important questions. It provides a broad overview of skill mismatch and the factors that contribute to it, analyses its economic and social costs, and argues why skill mismatch should be a concern for national and European policy-makers. As information across different countries is currently limited, the report also discusses how skill mismatch can be better approached and measured in surveys, with the aim of enabling more detailed and sound analyses in the coming years." (Hrsg., BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; G 1.3.1 Bildungsangebot & -nachfrage; G 1.2.3 Qualifikationsentwicklungen; I 2.2 Europa; Berufliche Qualifikation; Qualifikationsbedarf; Mismatch; Fachkräftemangel; Unterqualifikation; Überqualifikation; Qualifikationsforschung; Europa